Implementasi Kebijakan Penilaian Berbasis Literasi Membaca Pada Mata Pelajaran Pendidikan Pancasila Di Sma Wachid Hasyim 2 Taman Sidoarjo - Sekaryati, Hanadya; Harmanto (Universitas Negeri Surabaya (Unesa), 2024)
This study aims to describe the implementation of reading literacy-based assessment policies in Pancasila Education subjects at Wachid Hasyim 2 High School Taman Sidoarjo. The research method used is a qualitative approach with a case study research design because of the school's policy regarding literacy-based assessment in all subjects, especially those that lead to the form of AKM questions. Data was collected through documentation, interviews and observations. Data analysis techniques with the Miles and Huberman model. The results of the study show that the implementation of the policy begins with the Principal issuing a Decree (SK) to all subject teachers to include AKM questions in summative assessment. Then, the Principal appointed the Deputy Principal of the Curriculum section as the coordinator of policy implementation. In conveying policies to teachers, the Vice Principal of the Curriculum Division collaborates with the school Curriculum Development Team in conducting workshops for teachers, providingbriefings and becoming proofreaders of questions made by teachers. Teachers of Pancasila Education subjects themselves in implementing the policy develop questions from three aspects, namely content, cognitive processes and context. The content applied in the form of informational text/article text as a stimulus, from the text then directs students to be able to find information in the text, process what has been read and associate it with the knowledge they have. Meanwhile, the context provided can be related to the daily life of students, current events or only about learning materials. This shows that the distribution of responsibilities in the variables of the bureaucratic structure is going well.